ChemInform Abstract: Acid Catalyzed Nitrile Thiolysis of 3‐Amino‐acrylonitriles, Toward the Synthesis of 3, 4‐Substituted‐5‐amino‐isothiazoles. Issue 36 (September 2015) - Kuklish, Steven L.; Backer, Ryan T.; Fisher, Matthew J.; Kempema, Aaron M.; Mauldin, Scott C.; Merschaert, Alain
Abstract The use of an acid‐catalyzed thioamidation of unsaturated nitriles for the preparation of substituted‐5‐amino‐isothiazoles, providing a useful complement to the known base‐catalyzed procedures.